2017
DOI: 10.1007/s10570-017-1609-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xylanases on refining process and kraft pulp properties

Abstract: Results of this study demonstrate that enzymatic pretreatment of pulps enables energy savings in the refining process. Pretreatments of NBSK pulp with 3 different commercial xylanases resulted in a faster increase in the pulp freeness that reduced energy input for refining. The partial xylan removal by these enzymes affected the properties of cellulosic pulp and paper. The tensile properties of paper were improved by pretreatment with a pure xylanase while the additional activity of cellulases in the other two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
(19 reference statements)
1
3
0
1
Order By: Relevance
“…6e). Therefore, since dosed at identical endoglucanase activities based on cellopentaose, this indicates the important role of this activity in refining in accordance with some previous studies (Pere et al 1997). Furthermore, the fact that the release of reducing sugars cannot be used as a parameter for dosing refining enzymes was confirmed similarly to what was previously reported in several studies (Gil et al 2009;Wu et al 2020).…”
Section: Effect Of Enzyme Formulations and Purified Endoglucanases On Refiningsupporting
confidence: 89%
See 2 more Smart Citations
“…6e). Therefore, since dosed at identical endoglucanase activities based on cellopentaose, this indicates the important role of this activity in refining in accordance with some previous studies (Pere et al 1997). Furthermore, the fact that the release of reducing sugars cannot be used as a parameter for dosing refining enzymes was confirmed similarly to what was previously reported in several studies (Gil et al 2009;Wu et al 2020).…”
Section: Effect Of Enzyme Formulations and Purified Endoglucanases On Refiningsupporting
confidence: 89%
“…The highest protein concentrations were measured in EnzC (254 mg mL -1 ) followed by EnzB (176 mg mL -1 ), while EnzA exhibited the lowest protein concentration of 27.1 mg mL -1 . All enzyme preparations showed endoglucanase activity which has been reported to play a major role in refining of pulps (Pere et al 1997). However, activities measured on the endoglucanase specific CellG5 substrate (derivatized cellopentaose) varied over a wide range from 1.3 nkat mg -1 (EnzA) to 13.7 nkat mg -1 for EnzC (Fig.…”
Section: Comparison Of Refining Enzyme Formulationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Nilai derajat giling pulp A. mangium cenderung lebih rendah dibandingkan E. pellita, derajat giling pulp A. mangium sekitar 570-590 mLCSF sedangkan E. pellita sekitar 630-640 mLCSF. Derajat giling yang tinggi cenderung memerlukan energi yang lebih besar untuk menurunkan nilai derajat gilingnya agar laju penghilangan airnya sesuai dengan target yang diharapkan (Buzała et al, 2018). Pulp A. mangium memerlukan jumlah putaran sekitar 4.900-5.200 dan E. pellita sekitar 5.200-5.300 untuk mencapai nilai derajat giling yang sama (300 mL CSF).…”
Section: Derajat Giling (Freeness)unclassified
“…Studies have shown that the tensile index and energy absorption of the xylanase-treated wheat straw do not increase; however, its tear index decreases significantly [ 19 ]. Xylanase enhances the bleaching process and has a positive impact on pulp, paper and wastewater treatment, aiming to reduce the use of bleaching chemicals in the pulp refining process [ 6 , 20 ].…”
Section: Introductionmentioning
confidence: 99%